2016
DOI: 10.20546/ijcrbp.2016.304.009
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Plant Densities and Age of Seedlings on Dry Matter Partitioning and Grain Yield Potential of Transplanted Rice (Oryza sativa L.)

Abstract: A b s t r a c t A r t i c l e I n f oAn experiment was carried out during kharif, 2013 at College Farm, Rajendranagar, Hyderabad. with three plant densities (1 seedling hill -1, 3 seedlings hill -1 , 5 seedlings hill -1 ) as factor one and four age of seedlings (15 days old seedlings, 25 days old seedlings, 35 days old seedlings, 45 days old seedlings) as factor two in randomized block design, replicated thrice. Experimental results showed 5 seedlings hill -1 was found to be significant to get more productive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 2 publications
1
4
0
Order By: Relevance
“…Machine transplanting ensures timely planting in the season and relieve women labor from drudgery with an additional net return of Rs 11000/ha (15.7%). These results are in accordance with Shukla et al [9], Vijayalaxmi et al [10].…”
Section: Resultssupporting
confidence: 92%
“…Machine transplanting ensures timely planting in the season and relieve women labor from drudgery with an additional net return of Rs 11000/ha (15.7%). These results are in accordance with Shukla et al [9], Vijayalaxmi et al [10].…”
Section: Resultssupporting
confidence: 92%
“…Singh and Husain (1983) also reported increased rice growth parameters with planting of 25-30 days old seedlings and mentioned that younger seedlings had lower effective tiller rate and prone to mechanical damage when compared with higher aged seedlings. Vijayalaxmi et al, (2016) reported 25 days old seedlings as the optimum age as for higher DMP with highest partitioning towards panicle followed by stem and leaf.…”
Section: Age Of Seedlingsmentioning
confidence: 97%
“…Whereas, transplanting of 4 to 5 seedlings hill -1 resulted in production of weak panicles with less filled spikelets. Optimum plant density for higher DMP and grain yield would be 5 seedlings hill -1 which produced higher DM with highest partitioning towards panicle followed by stem and leaf (Vijayalaxmi et al, 2016).…”
Section: Number Of Seedling Per Hillmentioning
confidence: 99%
“…Mahajan et al [43] reported that significantly more grains/panicle, higher test weight and grain yield were recorded when basmati rice was transplanted on 10 th July. [44,45]. A subsequent delay in transplanting i.e.20 th and 30 th July, resulted in reduced grain yield by 8.4 and 27.1 per cent respectively as compared to 10 th July transplanting.…”
Section: Effect Of Dates Of Transplanting On Yield and Yield Contribu...mentioning
confidence: 98%